Determination of selected chemical properties of some oil press biproducts - ENAAM SARDAL ZAHR; ALAA GAZI EDAN AL-HASHIMI (University of Thi-Qar Journal of agricultural research, 2023)
A selected chemical properties including moisture, ash, carbohydrates, fat, protein and fiber, were studied in sesame, flax, black seed, coconut, star anise and sunflower using cold pressing method. An increase in moisture, ash, carbohydrates, protein and fiber was found after removing the oil. The amount of oil decreased as a result of extraction, the mineral content of the by-products, was also determined (calcium, magnesium, manganese, copper, iron, sodium and potassium), using an atomic absorption spectrophotometer. The defatted flaxseeds had the highest percentage of calcium, magnesium and manganese, compared with the rest of the de-oiled oil crops study. The essential and non-essential amino acids of the de-oiled oil crops were also determined by HPLC.